Microwave-Assisted Preparation and Characterization of Natural Rubber-Modified Sodium Montmorillonite-Poly (Methylmethacrylate) Interpenetrating Polymer Network Nanocomposites - Mohamad Zamri, Sharil Fadli (2008)
In this study, sodium montmorillonite (Na-MMt) was modified by dodecylamine (DDA) to produce dodecylamine montmorillonite (DDA-MMt). Elemental analysis result shows the amount of the surfactant intercalated in the DDA-MMt based on Carbon and Nitrogen content are 1.45 mmole/g and 1.38 mmole/g, respectively. The presence of alkyl ammonium in the DDA-MMt was analyzed by Fourier transform infrared (FTIR) analysis spectroscopy. X-ray Diffraction (XRD) pattern of DDA-MMt shows that the basal spacing of Montmorillonite (MMt) was expanded from 12.9 Å for the Na-MMt to 17.8 Å. The thermogravimety analysis (TGA) shows that DDA-MMt has an organic content which is equivalent to the mass of the intercalated DDA. Dicumyl peroxide (DCP) was used as curing agent for the natural rubber (NR). The scorch time of cured NR decreases when the DCP content is increased from 1.0 to 2.5 phr then levels off for further increase of the DCP content. Meanwhile, the torque difference and the curing time increase with the increase of the DCP concentration of from 1.0 to 3.5 phr. The tensile strength increases with increase of the DCP concentration from 1.0 up to 2.5 phr. However, addition of DCP beyond 2.5 phr decreases the tensile strength drastically. The percentage of gel content of the cured NR increases with the increase of the DCP content from 0.0 to 1.0 phr and slightly enhances with further addition of peroxide until 3.5 phr. TGA shows that the thermal stability of the cured NR improves with the increase of the DCP concentration. Dynamic mechanical analysis (DMA) indicates that the glass transition temperature (Tg) and the storage modulus (E’) of cured NR increase with DCP concentration increased. Preparation of the nanocomposites was carried out by melt blending of DDA-MMt and NR in a two-roll-mill internal mixer. The compounded natural rubber was then blended again with DCP and cured using an electric hydraulic hot press. Preparation of macrocomposites was also carried out using the same process but Na-MMt was used as the filler. The study shows that the scorch time of nanocomposites containing 1.0 to 7.0 phr DDA-MMt is higher than that of the macrocomposites. Increase the DDA-MMt concentration beyond to 7.0 phr lowers scorch time. Meanwhile, the different torque of the nanocomposites is higher than that of the macrocomposites. However, the curing time of the nanocomposites is lower than curing time of the macrocomposites. The FT-IR spectra reveal that the existence of DDA-MMt in the nanocomposites. The tensile strength, percentage of elongation at break and thermal degradation of the nanocomposites vary with the DDA-MMt content. DMA shows that Tg of the nanocomposites is lower than that of the cured NR and macrocomposites. It also found that their glass temperature decreases while storage modulus increases with increase of the clay content for both nanocomposites and macrocomposites. The percentage of gel content of the nanocomposites are higher than that of the macrocomposites at 1.0 phr DDA-MMt loading but decreases with addition of DDA-MMt up to 15.0 phr. Analysis of DDA-MMt dispersion by XRD and Transmission Electron Micrograph (TEM) shows that the DDA-MMt was intercalated and exfoliated in the NR matrix. The interpenetrating polymer network (IPN) nanocomposites were prepared by in situ microwave polymerization of methyl methacrylate (MMA) containing benzoyl peroxide (BPO) as initiator soaked in the cured NR/7phrDDA-MMt nanocomposite. The optimum conditions for the preparation of the IPN nanocomposites can be summarized as followed: 1% (w/w) of initiator concentration, 20 minutes polymerization and 1.5 hours soaking period. The FT-IR spectra of the IPN nanocomposites confirm that both nanocomposites and PMMA are exist in the IPN nanocomposites. The highest tensile strength of the IPN nanocomposites was observed when it is incorporated with 40 % (w/w) of PMMA. The percentage of the gel content of the IPN nanocomposites decreases with increase of the PMMA composition. The thermal stability of the IPN nanocomposites was determined and is in between thermal stability of PMMA and the nanocomposites. TGA also confirms that the thermal stability of the IPN nanocomposites is PMMA composition dependence. The tan δ against temperature curve of the IPN nanocomposites shows 2 Tgs which are around -46.90 to -39.88 ºC and 147.88 to 149.03 ºC which correspond to Tg of NR and PMMA, respectively. The storage modulus of the IPN nanocomposites increases with the increase of the PMMA composition. The XRD pattern of the IPN nanocomposites at 52, 35 and 7 % (w/w) of PMMA composition shows no diffractions peaks appeared in range of 2θ from 2 to 10º. TEM micrograph of IPN nanocomposites for both PMMA compositions shows that the DDA-MMt was exfoliated by which most of DDA-MMt platelets are distributed as a individual layer in the IPN nanocomposites matrix.